2020
DOI: 10.1371/journal.pcbi.1007972
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous, delayed-onset killing by multiple-hitting T cells: Stochastic simulations to assess methods for analysis of imaging data

Abstract: Although quantitative insights into the killing behaviour of Cytotoxic T Lymphocytes (CTLs) are necessary for the rational design of immune-based therapies, CTL killing function remains insufficiently characterised. One established model of CTL killing treats CTL cytotoxicity as a Poisson process, based on the assumption that CTLs serially kill antigen-presenting target cells via delivery of lethal hits, each lethal hit corresponding to a single injection of cytotoxic proteins into the target cell cytoplasm. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Consistently, we provide evidence for frequent delivery of sublethal hits in the TME. Our result implies that a high density of CTLs is most likely required for tumor regression, in order to increase the probability of killing (Deguine & Bousso, 2013;Halle et al, 2016;Hamieh et al, 2019;Beck et al, 2020). This has been indeed predicted by modeling approach (Budhu et al, 2010), and consistently, we had previously observed in two distinct models that tumor regression was associated with the progressive accumulation of cytotoxic effectors (Breart et al, 2008;Cazaux et al, 2019).…”
Section: Discussionsupporting
confidence: 85%
“…Consistently, we provide evidence for frequent delivery of sublethal hits in the TME. Our result implies that a high density of CTLs is most likely required for tumor regression, in order to increase the probability of killing (Deguine & Bousso, 2013;Halle et al, 2016;Hamieh et al, 2019;Beck et al, 2020). This has been indeed predicted by modeling approach (Budhu et al, 2010), and consistently, we had previously observed in two distinct models that tumor regression was associated with the progressive accumulation of cytotoxic effectors (Breart et al, 2008;Cazaux et al, 2019).…”
Section: Discussionsupporting
confidence: 85%
“…FASN-centered priming of cancer cells could also be considered to enhance the short lifespan and persistence of ACIs [268][269][270]. Contacts between cytotoxic immune cells and tumor cells are generally not binary 'life/death' events, but rather the damage done to cancer cells accumulates with multiple sublethal contacts with cytotoxic lymphocytes to reach a lethal threshold over time [271][272][273]. Importantly, mitochondria appear to be essential amplifiers of the death signal delivered by NK-cells and cytotoxic T-cells [274].…”
Section: Fasn Blockade: Reversing Immunoeditingdriven Metabolic Immun...mentioning
confidence: 99%
“…Following attempted or successful migration by an immune cell 𝑝, it can interact with other cells. Recent studies have shown support for the "multiple hit" hypothesis, in which target cells require multiple contacts from cytotoxic lymphocytes before death (53). Recently, it has been shown that cells can recover from sublethal damage caused by interactions with cytotoxic lymphocytes, with those receiving two or more "hits" displaying accelerated apoptosis induction (54).…”
Section: Cell-cell Interactionsmentioning
confidence: 99%